Clarifying the distal to proximal tephrochronology of the Millennium (B–Tm) eruption, Changbaishan Volcano, northeast China - Chen, X; Blockley, S; Tarasov, P; Xu, Y; McLean, D; Tomlinson, E; Albert, P; Liu, J; Müller, S; Wagner, M; Menzies, M (Elsevier, 2016)
Tephra dispersed during the Millennium eruption (ME), Changbaishan Volcano, NE China provides one of the key stratigraphic links between Asia and Greenland for the synchronization of palaeoenvironmental records. However, controversy surrounds proximal-distal tephra correlations because (a) the proposed proximal correlatives of the distal ME tephra (i.e. B-Tm) lack an unequivocal chronostratigraphic context, and (b) the ME tephra deposits have not been chemically characterized for a full spectrum of element using grain-specific techniques. Here we present grain-specific glass chemistry, including for the first time, single grain trace element data, for a composite proximal sequence and a distal tephra from Lake Kushu, northern Japan (ca. 1100 km away from Changbaishan). We demonstrate a robust proximal-distal correlation and that the Kushu tephra is chemically associated with the ME/B-Tm. We propose that three of the proximal pyroclastic fall units were erupted as part of the ME. The radiocarbon chronology of the Kushu sedimentary record has been utilised to generate a Bayesian age-depth model, providing an age for the Kushu tephra which is consistent with high resolution ages determined for the eruption and therefore supports our geochemical correlation. Two further Bayesian age-depth models were independently constructed each incorporating one of two ice-core derived ages for the B-Tm tephra, providing Bayesian modelled ages of 933-949 and 944-947 cal AD (95.4%) for the Kushu tephra. The high resolution ice-core tephra ages imported into the deposition models help test and ultimately constrain the radiocarbon chronology in this interval of the Lake Kushu sedimentary record. The observed geochemical diversity between proximal and distal ME tephra deposits clearly evidences the interaction of two compositionally distinct magma batches during this caldera forming eruption.